Ejecución presupuestaria del Gobierno Regional de Loreto y su relación con el desarrollo económico durante el periodo 2007 – 2019 - Tanchiva Sevillano, Andrea Madeleine (2023)
Loreto is one of the regions with the lowest economic growth in the country, and according to the INEI, it has one of the highest rates of child malnutrition and the lowest levels of schooling and education, therefore, to obtain higher growth rates , it is necessary to increase economic development, increasing the level of human capital of the population, increasing the level of education, better conditions and levels of health, as well as decent employment. In this sense, the objective of the work was to determine the relationship between the budgetary execution of the Regional Government of Loreto and the economic development of the Loreto region, during the period 2007 - 2019. For this, we developed an investigation of a quantitative nature, of a non- experimental and correlational design, where we find that there is a direct relationship between economic development and budget execution in the department of Loreto, during the period 2007 - 2019.